2011
DOI: 10.1002/jhm.964
|View full text |Cite
|
Sign up to set email alerts
|

Adverse outcomes associated with delayed intensive care unit transfers in an integrated healthcare system

Abstract: BACKGROUND: Patients with intensive care unit (ICU) transfers from hospital wards have higher mortality than those directly admitted from the emergency department. OBJECTIVE: To describe the association between the timing of unplanned ICU transfers and hospital outcomes. DESIGN, SETTING, PATIENTS: Evaluation of 6369 early (within 24 hours of hospital admission) unplanned ICU transfer cases and matched directly admitted ICU controls from an integrated healthcare system. Cohorts were matched by predicted mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
109
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(115 citation statements)
references
References 36 publications
4
109
1
1
Order By: Relevance
“…17 We postulate that there are likely systemrelated and patient-related factors that influence this relationship and contribute to what has come to be known as Bfailure to rescue.^1 8,19 System-related factors may include general inpatient floor staffing models and provider-patient ratios, 20 temporal issues including the time of day and day of the week at which deterioration occurs, 21 adherence to vital sign monitoring protocols, 22 and ICU bed availability. 7,23,24 There are also cultural barriers preventing staff from calling for assistance, [25][26][27][28] and nurse/physician providers often do not accurately self-assess the quality of their care for clinically deteriorating patients. 28 Patient factors, such as severity of illness, age, 29 medical comorbidities, and the number and type of specific criteria heralding deterioration 12,13,30 may all play a role as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 We postulate that there are likely systemrelated and patient-related factors that influence this relationship and contribute to what has come to be known as Bfailure to rescue.^1 8,19 System-related factors may include general inpatient floor staffing models and provider-patient ratios, 20 temporal issues including the time of day and day of the week at which deterioration occurs, 21 adherence to vital sign monitoring protocols, 22 and ICU bed availability. 7,23,24 There are also cultural barriers preventing staff from calling for assistance, [25][26][27][28] and nurse/physician providers often do not accurately self-assess the quality of their care for clinically deteriorating patients. 28 Patient factors, such as severity of illness, age, 29 medical comorbidities, and the number and type of specific criteria heralding deterioration 12,13,30 may all play a role as well.…”
Section: Discussionmentioning
confidence: 99%
“…1 The early period of deterioration may represent a time at which admission to the intensive care unit (ICU) is associated with improved survival, 2 particularly among patients who experience deterioration after admission to the hospital. 3 The existing studies examining the relationship between the delay from onset of clinical deterioration to ICU transfer and mortality were conducted over a decade ago, 4,5 did not examine the role of delays in care escalation, 6 or were restricted to the first 48 h of hospitalization, 7 collectively precluding a contemporary understanding of the impact of such delays throughout a hospital stay.…”
Section: Introductionmentioning
confidence: 99%
“…However, further investigation into the incidence and prognosis associated with these criteria in ward patients is essential for several reasons. First, many patients who develop sepsis are initially treated on the wards (14), and it has been shown that patients admitted to the ICU from the wards have a higher mortality rate than those admitted to the ICU from the emergency department (15,16). Second, many hospitals are now expanding their sepsis screening programs to the wards (17)(18)(19), and so information regarding the incidence and prognostic value of these criteria would inform these efforts.…”
mentioning
confidence: 99%
“…These comorbidities may not be identified in the acute care setting, which leads to worse clinical outcomes, increased length of stay, and increased cost [1][2][3][4][5]. Interdisciplinary rehabilitation improves outcomes and reduces length of stay when appropriately implemented [6].…”
Section: Introductionmentioning
confidence: 99%